“ANALISIS PENGARUH LEVERAGE, PROFITABILITAS, LIKUIDITAS, UMUR OBLIGASI DAN REPUTASI AUDITOR TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2017” - Dhikaton Putra Agustian, 14.05.52.0171; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
This Study is examine and analyze the effect of leverage, profitability, liquidity, matury and reputation auditor of the bond rating on the manufacturing companieslisted on the Indonesia Stock Exchange in the period 2013-2017. This study used purposive sampling method in sample selection, the criteria for a sample of the manufacturing companies listed in Indonesia Stock Exchange (IDX) during the period 2013-2017. Based on these criteria, obtaineda sample of 123 companies over a four-years observation period. Relationship and or influence between variable explained by using logistic regression analysis method. Result of research idicate that leverage variable and matury have negative effect not significant to bond rating, profitability and liquidity variable have positive effect not significanttobond rating, the variable of auditor reputation have a significant positive effect to bond rating. Keyword : Bond Rating, Leverage, Profitability, Liquidity, Matury, Auditor Reputation, Logistic Regression.